Water and Nutrient Scheduling for Drip Fertigated Rasthali (AAB) Banana - Abraham, Mini; S., Bhindhu P.; Thomas, Deepa; Joseph, Shyla (Journal of Tropical Agriculture, 2023)
A field experiment was conducted at Agronomic Research Station, Kerala Agricultural University, Chalakudy during 2017-2020 to study nutrient scheduling for drip fertigation under various irrigation levels for banana var. Poovan (Rasthali AAB). The experiment was laid out in factorial RBD with three levels of irrigation (I1 @ 50% Pan Evaporation (PE), I2 @ 75% PE, and I3 @ 100% PE) and three levels of fertigation (F1 @100% recommended dose of fertilizer (RDF) of Kerala Agricultural University (KAU), F2 @ 75% RDF and F3 @ 75% RDF along with 25% foliar application). These treatments were compared with farmers practice (control) that include basin application of water once in six days and soil application of fertilizers at 2 and 4 months after planting. Fertilizer application was scheduled with P as soil application and nitrogen and potassiumas drip fertigation at weekly intervals. Results of the experiment conducted for three years showed that irrigation @ 75% PE and fertigation @75% RDF could give significantly higher yield, water productivity, nutrient use efficiency and benefit cost ratio. Effect of fertigation showed significant influence on bunch weight and number of fingers. Bunch weight in F2 @ 75% drip fertigation (11.68kg/plant), was on par with F3 (11.926 kg) in which 75% drip fertigation + 25% foliar spray was given. Bunch weight in the treatment F2 was 30% increase over the control.